Evaluasi Kerusakan Permukaan Jalan Menggunakan Metode Bina Marga Dan Perioritas Penanganan Berdasarkan Nilai BCR Pada Kelas Jalan Provinsi Di Kota Depok - Marlyn Rosanne Uspessy; Andi Tenrisukki Tenriajeng (Rekayasa Sipil, 2022)
Infrastructure development of roads is one of the program to overcome the problem of high traffic the increasing volume of vehicles .This increase led to its complete destruction that occurs in road aside caused by natural factors, so needs a method to overcome the issues. This study uses the method Bina Marga to analyzed levels of the percentage of road damage and the determination of handling priority scores Benefit Cost Ratio .Based on the results of survey and analysis roads and the results of the value of benefit cost ratio, Jl .SP .Tole Iskandar - Pondok Rajeg has the Â highest value of the level damage and the largest value is 1,5. So, it is a priority to be handled first.